The Elderly’s Satisfaction with the Service Quality of a Community Geriatric Health Programme in Indonesia: a Cross-Sectional Study - Nursalam Nursalam; Mochamad Cholid Hanafi; Elida Ulfiana (Jurnal Ners, 2017)
Introduction: The achievement of the geriatric health programme is still under a number of government targets and the research about the satisfaction of elderly in contributing to this program still limited. This study aims to identify the correlation between the service quality of a geriatric health programme in the community with the satisfaction of older adults.Methods: The research design was cross-sectional and involved 277 elderly people as the respondents. The service quality was measured using a service quality (SERVQUAL) questionnaire with three different sub-variables of input, process and outcome. The elderly people’s satisfaction was examined using several parameters including reliability, assurance, tangibles, empathy and responsiveness (RATER). The data obtained from the questionnaires was analysed using the Spearman Rho test with a significance level of <0.05 to determine the correlation between the variables.Results: Good service quality provided satisfaction among the elderly. The Spearman Rho test result for input quality was p = 0.000 with a correlation coefficient of 0.705, while the test result for process quality was p = 0.000 with a correlation coefficient of 0.750. The outcome quality was p = 0.000 with a correlation coefficient of 0.766. The results showed that there is a relationship between the independent and dependent variables.Conclusions: Good service quality regarding the input, process and output of the service can enhance the satisfaction levels of the elderly. This study can be referred to as a parameter and evaluation for the PHC to maintain and improve the service quality standards for the elderly.